Czynniki determinujące zdrowy styl życia w opinii młodych konsumentów - Mucha, Beata; Mucha, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article concerns the healthy lifestyle of young consumers. The aim of the work was to determine the relationship between income and healthy lifestyle of young consumers. A healthy lifestyle is determined not only by the individual needs, but also by economic factors, which primarily include the income obtained and the price of products and services. The first part of the article presents the theoretical aspects of a healthy lifestyle. The empirical part of the publication, in turn, includes the results of one’s own research. The conclusion resulting from maintaining a healthy lifestyle of young consumers is that a healthy lifestyle is to some extent determined by the amount of income.
Keywords: young consumers; healthy lifestyle; healthy and organic food; physical activity